EVALUATION OF DIFFERENT COMBATING COMBINATIONS AGAINST LEAF-CUTTING ANTS IN Eucalyptus urograndis PLANTINGS - Vicentini, Fellipe Soares; Sousa, Nilton Jose; Koehler, Henrique Soares; Arce, Julio Eduardo; Ribeiro, Richardson; Behling, Alexandre (Floresta, 2024)
Leaf-cutting ants, genera Atta and Acromyrmex, are one of the main pests in forestry crops. They can affect forest productivity and increase mortality rates in plantations, making their control essential. Thus, this study aimed to evaluate different treatments for combating leaf-cutting ants and their results on the forest inventory of survival. Six treatments were evaluated in an area of approximately 14.000 hectares of Eucalyptus urograndis (Eucalyptus urophylla S. T. Blake × Eucalyptus grandis W. Hill), namely: 1) control, 2) pre-harvest combat, 3) pre-planting combat, 4) two or more pre-planting combats, 5) pre-harvest and pre-planting combat, and 6) pre-harvest combat with two or more pre-planting combats. The analyzed variables were: planted area (ha), planting survival (%), dead attacked seedlings (%), live attacked seedlings (%), and total attacked seedlings (%). Treatment comparisons were conducted using multivariate analysis of variance and discriminant analysis. Treatments that involved combat against ants only before harvesting or combined with pre-planting showed the best performance among the evaluated treatments. The most efficient treatment was the one that combated the ants before harvesting with just one repetition, resulting in reduced silvicultural costs.